Effects of the pre-show, at-show and post-show firm activities on trade show performance measurement - ÇOBANOĞLU, EMİNE (ELSEVIER SCIENCE BV, 2014)
Literature on trade show has been widening recently as with the acceleration of globalization trade shows are viewed not only as sales and promotion tools utilized by companies but also as a marketing strategy that integrates sales and promotion of company products and services, developing relationship building both with local and international customers and other stakeholders, increasing and sustaining the company image, benchmarking the company by analyzing the competition in the market, etc. Participation in international trade shows creates an excellent opportunity of entering new markets for firms and especially for SMEs which lead to the increase in their export thus easing the internationalization of their business. Within the context of this study, we aim to reveal empirical evidence of trade show performance measurement that is said to be effected by various firm activities conducted at pre-show, at-show and post-show stages of the trade show. As the method of data collection primary data collection was used with a development of a questionnaire which was conducted on a sample constituting of 124 firms 112 of which are SMEs at three international trade shows held in Istanbul, Turkey in 2013. Key findings are that sales-related and information-gathering performances are the most important for Turkish SMEs whereas at least one component from each stage of the trade show effect these performances. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: Trade show; trade show performance measurement; SMEs; marketing strategy; ANTECEDENTS